2016
DOI: 10.5902/1980509822744
|View full text |Cite
|
Sign up to set email alerts
|

GERMINAÇÃO DE SEMENTES E EMERGÊNCIA DE PLÂNTULAS DE <i>Luehea divaricata</i> Mart. et. Zucc. EM DIFERENTES SUBSTRATOS

Abstract: RESUMOO presente trabalho teve como objetivo avaliar diferentes substratos na germinação de sementes e emergência de plântulas de Luehea divaricata. O estudo foi realizado no Viveiro Florestal, DCFL, Universidade Federal de Santa Maria -RS. Os frutos foram coletados de oito árvores matrizes, no Morro do Cerrito, Santa Maria, em julho de 2010. Após o beneficiamento, as sementes permaneceram armazenadas em câmara fria, dentro de sacos de papel, por 4 meses, para o estudo de emergência de plântulas, e por 7 meses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
1
3
0
7
Order By: Relevance
“…issue that hinders the propagation of the Luehea divaricata is the germination rate of collected seeds. In a germination test performed on blotting paper, the germination rate of a seed lot collected in 2010 and stored for 7 months was only 27% (DUTRA et al, 2016), which confirmed results of previous studies that reported that the seed germination of Luehea divaricata is very variable, ranging between 20% and 75% (LORENZI, 2008). Thus, the minicutting technique may be away to overcome difficulties in propagating native species, especially species with seeds that are difficult to obtain and germinate, such as Luehea divaricata.…”
Section: Forestry Sciencesupporting
confidence: 87%
“…issue that hinders the propagation of the Luehea divaricata is the germination rate of collected seeds. In a germination test performed on blotting paper, the germination rate of a seed lot collected in 2010 and stored for 7 months was only 27% (DUTRA et al, 2016), which confirmed results of previous studies that reported that the seed germination of Luehea divaricata is very variable, ranging between 20% and 75% (LORENZI, 2008). Thus, the minicutting technique may be away to overcome difficulties in propagating native species, especially species with seeds that are difficult to obtain and germinate, such as Luehea divaricata.…”
Section: Forestry Sciencesupporting
confidence: 87%
“…(Gladunova et al, 2016), Hieracium pratense (Panebianco & Willemsen, 1976), H. aurantiacum L., H. praealtum L. (Bear et al, 2012). Sand substrate looks to be an appropriate substrate for seed germination of different alien and native species (e.g., Gladunova et al 2014Gladunova et al , 2016Dutra et al 2016;Radivojevic et al 2016). Therefore, it may be suggested that the germination rate would be higher on a sand substrate, like where this plant grows in the Mordovia Reserve.…”
Section: Resultsmentioning
confidence: 99%
“…Resultados inferiores foram encontrados por Silva et al (2014) aqueles que não ultrapassaram os 66% de germinação. Dutra et al (2016) também apresentaram resultados inferiores ao testarem a germinação de sementes de açoita cavalo (Luehea divaricata) com os substratos rolo de papel, sobre papel mataborrão, entre papel mata-borrão, sobre areia e sobre vermiculita, não conseguiram resultados superiores a 42% de germinação. Tais resultados demonstraram como cada espécie se adapta diferentemente com cada tipo de substrato, de maneira que para o presente trabalho o uso de papel, tanto sobre como entre, apresentaram resultados superiores, sendo estes os mais indicados para o uso no teste de germinação de aveia branca, ao contrário do trabalho citado anteriormente onde estes substratos não apresentaram resultados maior que 27%.…”
Section: Resultsunclassified